Experimental investigation the effect of nanofluid on the pressure drop across the solar collector - Nurshahiera, Mohidin (2013)
This is a study on the performance of a pressure drop system of a evacuated tube solar collector. The objective of this project is to analysis the effect of nanofluid as the working fluid and temperature on the pressure drop by determining the pressure drop by using distilled water and nanofluid at different flow rate. The existing solar system installed in UMP Pekan does not measure the pressure drop. Various working fluid and mass flow rate was use in order to measure pressure drop. The experiment is conducted at solar system installed at UMP Pekan and the data is collected at three hour time interval which is at 9 am, 12 pm and 3 pm. The data analysed using the theoretical analysis and plotted in graph to discuss about it. The pressure drop obtained for nanofluid in this experiment is higher than distilled water. The minimum pressure drop within this experiment for distilled water and nanofluid is 694 Pa and 989 Pa respectively. The maximum pressure drop within this experiment for distilled water and nanofluid is 2336 Pa and 2390 Pa respectively. The pressure drop increase as the temperature increase. Within in this experiment for both working fluid the pressure drop is lowest at 9 am which is at that time temperature is the lowest. Although all the above findings refer to a particular flow rate which is for flow rate 2 , 2.5, 3.0, 3.5 litre/min, the better results can be obtained if the flow rate is varied. Finally by considering the problem of accuracy of the result, pressure transducer should be used instead of used manometer to measure the pressure drop.